Range extension of the Bengal monitor (Varanus bengalensis) for the Trans-Himalayan Region with an altitude record for monitor lizards - Singh, Ashutosh; Rana, Bhupinder Singh; Thakur, Mukesh; Tripathy, Basudev; Sharma, Lalit Kumar; Chandra, Kailash (Zootaxa, 2020)
The Bengal monitor lizard or Common Indian monitor lizard (Varanus bengalensis Daudin, 1802) is classified as Least Concern under the IUCN and listed under the Schedule-I of the Indian Wildlife Protection Act 1972. Further, the trade of the species is prohibited as the species is listed in Appendix I of CITES. It is widely distributed over Western Asia, the Indian Subcontinent, and Southeast Asia (Koch et al. 2013). It is reported to occupy both terrestrial as well as freshwater habitats from desert areas to floodplains, scrubland to forests, in different types of terrains at elevations below 1500m (Auffenberg 1994; Papenfuss et al. 2010). Body size of individuals varies from 61 to 175 cm from the tip of the snout to the end of the tail (Auffenberg 1994; Losos and Greene, 1998). Adults are generally grey or greenish-grey in color, with a ventral pattern of grey to black crossbars from the chin to the tail. Adult individuals are less contrasting and have a less distinct pattern than younger individuals. The species shows a sexual dimorphism, with males being heavier (around 7.18 to 10 kg) than females which are about 40% smaller in size (Papenfuss et al. 2010).